2019
DOI: 10.3390/biom9060249
|View full text |Cite
|
Sign up to set email alerts
|

Bioevaluation of Ranatuerin-2Pb from the Frog Skin Secretion of Rana pipiens and Its Truncated Analogues

Abstract: Antimicrobial peptides (AMPs) are considered as a promising agent to overcome the drug-resistance of bacteria. Large numbers of AMPs have been identified from the skin secretion of Rana pipiens, including brevinins, ranatuerins, temporins and esculentins. In this study, the cDNA precursor of a broad-spectrum antimicrobial peptide, ranatuerin-2Pb, was cloned and identified. Additionally, two truncated analogues, RPa and RPb, were synthesised to investigate the structure-activity relationship of ranatuerin-2Pb. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…There appears to be a minimal requirement for peptide length in order for it to be antimicrobial. During isolation of novel AMPs, some truncated peptides were found to be inactive [ 8 , 134 , 135 ]. Likewise, further truncation of the minimal antibacterial peptide KR-12 of human cathelicidin LL-37 led to inactive peptides such as RI-10 [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be a minimal requirement for peptide length in order for it to be antimicrobial. During isolation of novel AMPs, some truncated peptides were found to be inactive [ 8 , 134 , 135 ]. Likewise, further truncation of the minimal antibacterial peptide KR-12 of human cathelicidin LL-37 led to inactive peptides such as RI-10 [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the killing efficacy of 5-iodoindole, time-kill experiments were performed as previously described [5,37]. Briefly, overnight cultures of A. baumannii ATCC 17978 strain at a dilution of 1:100 inoculated in TSB were used for assays.…”
Section: Time-kill Kinetics Assaysmentioning
confidence: 99%
“…It has been reported that in contrast with the intact amino acid sequences of some AMPs from ranidae frogs, the truncated N-terminus exhibited outstanding efficacy with enhanced antimicrobial activity and weak cytotoxicity [7,[11][12][13][14][15][16]. For instance, esculentin-1a consists of 46 amino acid residues with a ranabox at the C-terminus, while its truncated 21-mer N-terminal fragment, esculentin-1a(1-21) exhibited significant antimicrobial activity and lower hemolytic activity [11].…”
Section: Chemical Synthesis Of Br2gk and Design Of Derivativesmentioning
confidence: 99%